The Contributions of Lewis Fry Richardson to Drainage Theory, Soil Physics, and the Soil-Plant-Atmosphere Continuum - Raats, Peter A. C.; Knight, John H. (Frontiers in Environmental Science, 2018)
Lewis Fry Richardson (1881-1953) was an English polymath, who made important contributions to many fields, including numerical weather prediction, finite difference solutions of partial differential equations, turbulent flow and diffusion, fractals, and the cause and evolution of conflicts. In 1922 he published the book `Weather Prediction by Numerical Process'. He did the research for this book under difficult circumstances just before, during, and just after World War I. The book received a lot of attention initially, but methods like those proposed in it were not successfully implemented until the invention of fast digital computers around 1950. To model heat and mass transfer in the atmosphere, Richardson did much original work on turbulent flow and defined what is now known as the Richardson number. His technique for improving the convergence of a finite difference calculation is known as Richardson extrapolation, and was used by John Philip in his 1957 semi-analytical solution of the Richards equation for water movement in unsaturated soil. With the first draft of his book just finished, from mid-1916 the pacifist Richardson drove an ambulance in France during the later part of World War I. But even then, In his spare time, he did weather related experiments and computations, rewrote the first draft of his book, and started a new scientific career in the study of conflicts, again using existing and inventing new mathematical tools. Posthumously, most of Richardson$'$s contributions in various fields received considerable attention. But important exceptions are his contributions to soil science and hydrology, on which we focus in this paper. His first published papers in 1908 concerned the numerical solution of the free surface problem of unconfined flow of water in saturated soil, arising in the design of required ditch spacing for draining peat. He developed and used a graphical method to solve this problem. This and other practical problems stimulated his interest in numerical methods and soon led him to the challenge of numerical weather prediction. Richardson formulated an elaborate model for transport processes in the atmosphere. For the lower boundary of his atmospheric model he needed to understand the movement of liquid